2016
DOI: 10.1021/acsami.6b10201
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Coordination Polymer to Prepare Density Controllable and High Nitrogen-Doped Content Carbon/Graphene for High Performance Supercapacitors

Abstract: Design and preparation of carbon-based electrode material with high nitrogen-doping ratio and appropriate density attract much interest for supercapacitors in practical application. Herein, three porous carbon/graphene (NCG, NCG, and NCG) with high doping ratio of nitrogen have been prepared via directly pyrolysis of graphene oxide (GO)/metal-organic coordination polymer (MOCP) composites, which were formed by reacting 4,4'-bipyridine (BPD) with CuCl, FeCl, and ZnCl, respectively. As-prepared NCG, NCG and NCG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…23,25 HTC-NPG-C presents a type-II isotherm associated with a nonporous structure. 26,56 The PG-AC, HTC-PG-AC, and HTC-NPG-AC also show type-IV isotherms with steep rise in low relative pressure (P/P 0 < 0.1) and a type-H4 hysteresis loop in middle relative pressure (0.4 < P/ P 0 < 0.9), indicating the presence of abundant micropores and a certain amount of mesopores. 12,53,55 The slight increase of adsorption at high relative pressure (P/P 0 > 0.9) is associated with the presence of macropores.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…23,25 HTC-NPG-C presents a type-II isotherm associated with a nonporous structure. 26,56 The PG-AC, HTC-PG-AC, and HTC-NPG-AC also show type-IV isotherms with steep rise in low relative pressure (P/P 0 < 0.1) and a type-H4 hysteresis loop in middle relative pressure (0.4 < P/ P 0 < 0.9), indicating the presence of abundant micropores and a certain amount of mesopores. 12,53,55 The slight increase of adsorption at high relative pressure (P/P 0 > 0.9) is associated with the presence of macropores.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…So, the bonding configurations of heteroatoms in NP‐HPC‐x were further studied on the basis of a high‐resolution XPS spectrum. The N1s spectrum of NP‐HPC‐x can be assigned to four typical peaks located at 398.4, 400.1, 401.2, and 402.0–405.0 eV, corresponding to pyridinic, pyrrolic, graphitic, and oxidized pyridinic nitrogen, respectively . The results (Figure S2, Supporting Information) indicated that increasing carbonization temperature leads to a conversion from pyrrolic nitrogen to graphitic nitrogen .…”
Section: Resultsmentioning
confidence: 97%
“…[1,2] The EDLCs can store electrical energy by utilizing ion absorption/desorptionp rocesses between the electrolyte and electrode materials. [3,4] Generally,ahigh surfacea rea in the porouse lectrode materials is considered as an important factor to prepare high-performance EDLCs. [5] To develop ah ierarchicalp orousa rchitecture is another important strategy for the preparation of excellent supercapacitors.…”
Section: Introductionmentioning
confidence: 99%